2015
DOI: 10.1007/s00405-015-3865-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of multilevel upper airway surgery on CPAP tolerance in non-responders to obstructive sleep apnea surgery

Abstract: The aim of this study was to evaluate the influence of multilevel upper airway surgery on subsequent continuous positive airway pressure (CPAP) use and tolerance in patients with moderate to severe obstructive sleep apnea (OSA). The study cohort enrolled 67 consecutive patients, who underwent septoplasty plus modified uvulopharyngopalatoplasty (mUPPP) with or without modified tongue base suspension (mTBS) due to CPAP intolerance, and who had residual OSA requiring CPAP therapy [non-responders to surgery, apnea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…A meta-analysis of 1978 patients showed that the overall success rate was 66.4% in patients with multilevel sleep apnea surgery involving at least two anatomical sites: nose, oropharynx, or hypopharynx [ 13 ]. Furthermore, patients receiving postoperative CPAP had lower AHI and ESS scores and higher SpO 2 [ 14 ]. Azbay et al reported that approximately 48% of patients who cannot tolerate CPAP preoperatively can tolerate it postoperatively [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 1978 patients showed that the overall success rate was 66.4% in patients with multilevel sleep apnea surgery involving at least two anatomical sites: nose, oropharynx, or hypopharynx [ 13 ]. Furthermore, patients receiving postoperative CPAP had lower AHI and ESS scores and higher SpO 2 [ 14 ]. Azbay et al reported that approximately 48% of patients who cannot tolerate CPAP preoperatively can tolerate it postoperatively [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients receiving postoperative CPAP had lower AHI and ESS scores and higher SpO 2 [ 14 ]. Azbay et al reported that approximately 48% of patients who cannot tolerate CPAP preoperatively can tolerate it postoperatively [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPAP and surgery are not exclusive from each other; actually, they can have mutual benefits and reciprocity. For example, nasal, tongue base and multiple-level surgery can reduce CPAP pressure and improve CPAP compliance in OSA [22] , [23] , [24] . By contrast, CPAP can be used to stabilize airway after intrapharyngeal surgery especially in tongue surgery [25] .…”
Section: Principle In Decision-making Between Cpap and Surgerymentioning
confidence: 99%
“…Post-operatively, about 50% of the study sample reported that their symptoms were resolved, and about 50% tolerated CPAP without problems. On the other hand, Hui, et al investigated the therapeutic effects of a MAD combined with either nasal or pharyngeal surgery [6]. The AHI of the combined surgical group was significantly lower post-operatively, and the authors concluded that surgical enlargement of the nasal and pharyngeal airways combined with a MAD is an effective treatment in patients with severe OSA.…”
Section: Introductionmentioning
confidence: 99%